Correlation Knowledge and Attitude of Nurse Behaviour in Medical Waste Disposal in Inpatient Ward of The JIH Hospital Yogyakarta - Jennifa Jennifa; Dwi Agustiana Sari; Ertanti Anugraheni (Universitas Bondowoso, 2021)
Background: In Indonesia there is an increase in the amount of medical waste. Medical waste is still not managed properly and the amount is very large.Previous studies conducted found that nurses had less behavior in disposing both medical and non-medical waste (58,3%). Hospital waste management carried out by nurses and medical personnel, must be done properly and carefully. Method: This research was an analytic survey research with cross sectional approach. The population of this study were 150 nurses in the Inpatient Ward of JIH Hospital Yogyakarta. The sampling technique was simple random sampling, amounting to 60 people. The research instrument used questionnaire. The data analysis technique used chi-square test and logistic regression. Result: Nurses knowledge mostly in sufficient category (55%). Nurses attitude mostly in supportive category (56,7%). Nurses behavior mostly in good category (50%). There was correlation between knowledge and medical waste behavior with significant value 0,030 (p<0,05). There was correlation between attitudes and medical waste behavior with significant value 0,019 (p<0,05). Conclusion: There were correlations of knowledge and attitudes to the medical waste behavior on nurses in inpatient ward of JIH hospital Yogyakarta.